A systematic review of data protection and privacy preservation schemes for smart grid communications. (April 2018) - Ferrag, Mohamed Amine; Maglaras, Leandros A.; Janicke, Helge; Jiang, Jianmin; Shu, Lei
Highlights: We provide a classification of attacks of leaking privacy in smart grids. We present various countermeasures and game theoretic approaches. We present a side-by-side comparison in a tabular form for the current state-of-the-art of privacy-preserving schemes (thirty-two) proposed for smart grids. We present a discussion of technical challenges and open directions for future research. Abstract: In this paper, we present a comprehensive survey of privacy-preserving schemes for smart grid communications. Specifically, we select and in-detail examine thirty-two privacy preserving schemes developed for or applied in the context of smart grids. Based on both communication and system models, we classify these schemes that are published between 2013 and 2017, in five categories, including, (1) smart grid with advanced metering infrastructure, (2) data aggregation, (3) smart grid marketing architecture, (4) smart community of home gateways, and (5) vehicle-to grid architecture. For each scheme, we survey attacks of leaking privacy, countermeasures, and game theoretic approaches. In addition, we review survey articles published in the recent years that deal with smart grids communications, applications, standardization, and security. Based on the current survey, several recommendations for further research are discussed at the end of this paper.